1992
DOI: 10.1017/s0022215100119449
|View full text |Cite
|
Sign up to set email alerts
|

Adenoids: comparison of radiological assessment methods with clinical and endoscopic findings

Abstract: Methods of evaluating adenoidal size pre-operatively are controversial. Symptoms and clinical evaluation have been both advocated and condemned. Depending on the methodology, measurement of the radiological adenoidal shadow has been difficult to correlate with the clinical patency of the nasopharyngeal airway and to the actual size of the removed adenoid.Four different methods were used to measure the adenoidal size on 74 radiographs. The methods were evaluated against the degree to which the adenoids obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
1
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 12 publications
6
130
1
7
Order By: Relevance
“…There are reports of different radiographic methods for evaluation of nasopharynx, while the interpretation of presence or absence of adenoid hypertrophy is not a consensus among authors. According to Wormald et al who conducted a comparative study among methods, Cohen & Konak developed the best approach providing the highest positive predictive value 11 . According to these authors, their method takes into account the relation between nasopharynx and adenoid sizes, besides being a simple approach, once it does not require measures and calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of different radiographic methods for evaluation of nasopharynx, while the interpretation of presence or absence of adenoid hypertrophy is not a consensus among authors. According to Wormald et al who conducted a comparative study among methods, Cohen & Konak developed the best approach providing the highest positive predictive value 11 . According to these authors, their method takes into account the relation between nasopharynx and adenoid sizes, besides being a simple approach, once it does not require measures and calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment method developed in this study outstands for being an objective, easy and reproducible approach. Wormald et al report that, in doubtful cases, nasal endoscopy under local anesthesia provides a definitive evaluation of the nasal cavity and nasopharynx state 11 . Another study consistent with our findings showed that nasofibroscopy is more reliable than lateral x-ray of the paranasal sinuses to assess size and shape of pharyngeal tonsil 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Some authors feel that it is obstruction at the level of the choanae and nasopharynx rather than local infection that is the cause for persistent rhinorrhoea [8,9]. Tuncer et al [9] separately cultured maxillary sinus aspirates and adenoid tissue in children undergoing adenoidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the adenoid was determined with flexible fiberoptic endoscope. Adenoid obstructing the nasopharyngeal cavity by <50% was classified as small, adenoid obstructing the nasopharyngeal cavity by 50-75% was classified as moderate and adenoid obstructing the nasopharyngeal cavity by >75% was classified as large (14). >50% obstruction in the nasopharyngeal airway was considered as adenoid hypertrophy.…”
Section: Methodsmentioning
confidence: 99%